Shariah bank efficiency in Indonesia: Does competition matter? - Wulandari, Dewi Eka; Widarjono, Agus (Proceeding International Conference on Accounting and Finance, 2024)
This paper analyzes the influence of competition with bank-specific and macroeconomic variables as control variables in influencing the cost efficiency of Sharia commercial banks in Indonesia. Our research examines all Shariah banks (34 banks) from 2015 to 2020 using quarterly data. The estimation method is panel data regression. The results indicate that fierce competition causes an increase in the cost efficiency of Shariah commercial banks. However, the effect of competition on cost efficiency is more pronounced in full-fledged Shariah banks than in Shariah bank subsidiaries of conventional banks. Banks with strong fundamentals can encourage efficiency. For example, bank size, equity, and income diversification have a positive effect on bank efficiency. However, a high NPF reduces efficiency. Furthermore, negative external shocks such as Covid-19 reduce cost efficiency.